Kepemimpinan Kepala Sekolah dalam Penguatan Karakter Islami Peserta Didik: Studi Kualitatif di SDIT Al Fikri Sungai Penuh - Edi Sunarya; Puput Wahyu Hidayat (CV. Master Literasi Indonesia, 2026)
Character education has become one of the main priorities in Indonesian basic education, particularly in Islamic schools that integrate religious values into daily learning and school culture. In this context, the principal plays a strategic role in planning, organizing, implementing, and evaluating programs that strengthen students’ Islamic character. This study aims to describe the implementation of principal leadership in strengthening students’ Islamic character at SDIT Al Fikri Sungai Penuh. This research employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, and students. The data were analyzed using the Miles and Huberman interactive model, while data credibility was ensured through source and technique triangulation. The findings reveal that the principal plays an active role in planning, organizing, implementing, and evaluating Islamic character-strengthening programs integrated into the school's religious culture. The programs include congregational prayers, Qur'anic memorization, worship practices, habituation of Islamic manners, and school discipline. These programs positively influence students’ religiosity, discipline, responsibility, social awareness, and academic and non-academic achievements. The study concludes that effective principal leadership is a strategic factor in developing sustainable Islamic character education through a religious school culture, contributing to students’ holistic character development and improved educational outcomes.